Diagnosis, treatment, and response assessment in solitary plasmacytoma: updated recommendations from a European Expert Panel - Caers, J. (J Hematol Oncol, 2018)
Solitary plasmacytoma is an infrequent form of plasma cell dyscrasia that presents as a single mass of monoclonal plasma cells, located either extramedullary or intraosseous. In some patients, a bone marrow aspiration can detect a low monoclonal plasma cell infiltration which indicates a high risk of early progression to an overt myeloma disease. Before treatment initiation, whole body positron emission tomography–computed tomography or magnetic resonance imaging should be performed to exclude the presence of additional malignant lesions. For decades, treatment has been based on high-dose radiation, but studies exploring the potential benefit of systemic therapies for high-risk patients are urgently needed. In this review, a panel of expert European hematologists updates the recommendations on the diagnosis and management of patients with solitary plasmacytoma. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13045-017-0549-1) contains supplementary material, which is available to authorized users.